Cost and Benefit Analysis of Smallholder Pepper Production Systems. Issue 4 (3rd July 2016) - Ayodele, O. J.; Ajewole, O. C.; Alabi, E. O.
ABSTRACT: The economic potential of smallholder pepper ( Capsicum spp.) production needs clarification. A study was carried out with 60 farmers randomly selected from three districts of Ekiti State, Nigeria, to determine the cost-benefit ratio and feasibility of the practice. Frequency counts and percentages, means, and ranges of values were used to analyze the data and profitability. Pepper production was determined with gross margin and cost-benefit ratio. Most respondents were men, with an average age 42 years old, and most had at least formal primary education. Mean farm size was 0.09 ha and farmers averaged ~12 years' experience in pepper production. With a low yield (2.79 Mt·ha −1 ) and cost of ₦165, 478.00·ha −1 (N is Naira, Nigerian currency, US$1 = N183) to produce with a gross margin of ₦272, 175.22·ha −1, the benefit-cost ratio was 1.64. This profitability, compatibility with other arable crops in mixtures, low disease and pest problems, and high market demand provide incentives for pepper production. Inadequate capital, shortage of labor, lack of extension services, and nonavailability of fertilizers and improved planting materials were constraints to optimum yield and profitability.